Ewing Sarcoma of the Kidney: A Rare Entity. (9th January 2014) - Almeida, Maria Fernanda Arruda; Patnana, Madhavi; Korivi, Brinda Rao; Kalhor, Neda; Marcal, Leonardo
Abstract : Ewing sarcoma and primitive peripheral neuroectodermal tumor (PNET) are high-grade malignant tumors typically found in children and adolescents. These tumors belong to the family of small round cell tumors and are of neuroectodermal origin. Primary Ewing sarcoma of the kidney is rare and because of that is an infrequent differential diagnosis in urologic malignancies. Renal PNET mostly presents with nonspecific symptoms such as hematuria and abdominal pain. The imaging findings are uncharacteristic. The diagnosis is based on the histology, immunohistochemistry, and molecular pathologic findings. Once PNET has been diagnosed, multimodal treatment is indicated. Despite all treatment options, the prognosis of those with metastatic disease is poor.